2020
DOI: 10.1101/2020.10.18.344523
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Temporal changes in plasma membrane lipid content induce endocytosis to regulate developmental epithelial-to-mesenchymal transition

Abstract: Epithelial-to-mesenchymal transition (EMT) is a dramatic change in cellular physiology during development and metastasis which involves coordination between cell signaling, adhesion, and membrane protrusions. These processes all involve dynamic changes in the plasma membrane, yet how membrane lipid content regulates membrane function during developmental EMT remains incompletely understood. By screening for differential expression of lipid-modifying genes over the course of EMT in avian neural crest, we have i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…To better understand the molecular processes in which Draxin, and by extension canonical Wnt signaling, function during cranial neural crest EMT, we performed functional annotation for the dataset using the Database for Annotation, Visualization and Integrated Discovery (DAVID) ( Huang da et al, 2009a , b ). Consistent with established roles of canonical Wnt signaling and Draxin-mediated inhibition during cranial neural crest EMT, we observed enrichment of genes associated with transcriptional regulation, cell adhesion, and lipid synthesis, which we have recently shown is important for cell signaling during cranial neural crest EMT ( Piacentino et al, 2020 ). In addition, we found numerous genes associated with bone/cartilage formation (e.g., CYTL1 , ILK , NOV ), a critical function of cranial neural crest, and genes involved in ribosome biogenesis (e.g., NOP56 , PES1 , NOC2L ), which has implications for craniofacial development ( Ross and Zarbalis, 2014 ) ( Figure 3A ).…”
Section: Resultssupporting
confidence: 87%
“…To better understand the molecular processes in which Draxin, and by extension canonical Wnt signaling, function during cranial neural crest EMT, we performed functional annotation for the dataset using the Database for Annotation, Visualization and Integrated Discovery (DAVID) ( Huang da et al, 2009a , b ). Consistent with established roles of canonical Wnt signaling and Draxin-mediated inhibition during cranial neural crest EMT, we observed enrichment of genes associated with transcriptional regulation, cell adhesion, and lipid synthesis, which we have recently shown is important for cell signaling during cranial neural crest EMT ( Piacentino et al, 2020 ). In addition, we found numerous genes associated with bone/cartilage formation (e.g., CYTL1 , ILK , NOV ), a critical function of cranial neural crest, and genes involved in ribosome biogenesis (e.g., NOP56 , PES1 , NOC2L ), which has implications for craniofacial development ( Ross and Zarbalis, 2014 ) ( Figure 3A ).…”
Section: Resultssupporting
confidence: 87%
“…So, taking together these observations and our results, we can infer that during the aging process, the regulation of SM metabolism by nSMase may play a critical role in the EMT of CD cells of aged‐rats to generate renal fibrosis. Piacentino et al (2020) also demonstrated that at the beginning of the EMT, the conversion of SM into ceramide mediated by nSMase2 promotes membrane curvature. This facilitates the endocytosis of activated signaling complexes (Wnt and BMP) and leads to the activation of pro‐EMT transcriptional targets including Snail2, which promotes neural crest EMT and migration.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with our results, Hernandez‐Corbacho et al (2011) demonstrated that during aging, nSMase and ceramide synthase activities increase, and hexosylceramides and lactosylceramides accumulate in mouse kidney. Recently, Piacentino et al (2020) point to nSMase2 as a critical regulator of the EMT during neural development. So, taking together these observations and our results, we can infer that during the aging process, the regulation of SM metabolism by nSMase may play a critical role in the EMT of CD cells of aged‐rats to generate renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Cer and DAG were among the “green” lipids, strongly suggesting that they moderate the cancer effect. The neutral sphingomyelinase 2 enzyme has been shown to induce production of Cer, a sphingolipid component of ordered membrane domains, which induces receptor clustering and plasma membrane curvature in the neural crest during development (52, 59). Subsequent endocytosis of Wnt and BMP signaling complexes was sufficient to activate epithelial-to-mesenchymal transition, suggesting a key role for Cer in regulating cell migration.…”
Section: Discussionmentioning
confidence: 99%